PENGENALAN WARNA DAN BILANGAN MENGGUNAKAN MEDIA CAT AIR TERHADAP KECERDASAN KOGNITIF ANAK USIA 4 HINGGA 5 TAHUN - Sugito Muzaqi; Siti Nurhidayati (MOTORIC, 2021)
PAUD learning today must be fun and memorable for children, especially at the age of 4-5 years, children are able to recognize colors and symbols of numbers 1-10. However, at this age there are still those who cannot distinguish colors and call number symbols as the basis for learning for children. Due to monotonous learning using children's worksheets, making children bored and not understanding colors and numbers, therefore the researchers took the title "Introduction to Colors and Numbers Using Watercolor Media on Cognitive Intelligence of Children aged 4 to 5 Years". This study uses a quantitative research model and refers to the implementation process proposed by Kemmis and Mc.Taggart. For all the limitations, this research minimizes meetings so that the data collection process is only carried out for two meetings. The data obtained show an increase in children's cognitive abilities in understanding color and number material. This refers to the success percentage of 77.5%, which is growing rapidly during the second cycle of learning. Much improved compared to the previous learning which only involved writing instruments in the pre-action with 43.6% gain with sufficient predicate. Then again doing the first cycle of learning by using crayons won the percentage to 57%. Officially the criteria that can also turn out to be good.. Key word: Recognizing Colors and Numbers, Cognitive, and Watercolor